A new species of Mandevilla (Apocynaceae) from limestone outcrops in Central Brazil with a short note on the occurrence of geophytes in rauvolfioids and apocynoids - J. Francisco Morales; Mary E. Endress; Isa Lucia de Morais; Polla Renon (Acta Botânica Brasílica, 2023)
ABSTRACT Mandevilla calcicola, endemic to limestone formations in Goiás state, Brazil, is described. A key and photos for all Mandevilla species reported in Goiás and Distrito Federal, Brazil, are included. This new species is assessed as Critically Endangered (CR). A short note on the occurrence of geophytes in rauvolfioids and apocynoids (focused on Mandevilla) and its taxonomic value is included.